Proceedings of the Joint International Conference on Measurement and Modeling of Computer Systems 2004
DOI: 10.1145/1005686.1005702
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of LAS-based scheduling disciplines in a packet switched network

Abstract: The Least Attained Service (LAS) scheduling policy, when used for scheduling packets over the bottleneck link of an Internet path, can greatly reduce the average flow time for short flows while not significantly increasing the average flow time for the long flows that share the same bottleneck. No modification of the packet headers is required to implement the simple LAS policy. However, previous work has also shown that a drawback of the LAS scheduler is that, when link utilization is greater than 70%, long f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Size-based scheduling has received a lot of attention from the research community with applications to Web servers [15], Internet traffic [3,14,16] or 3G networks [2,10]. The key idea is to favor short flows at the expense of long ones because short flows are in general related to interactive applications like Email, Web browsing or DNS requests/responses; unlike long flows which represent background traffic.…”
Section: Introductionmentioning
confidence: 99%
“…Size-based scheduling has received a lot of attention from the research community with applications to Web servers [15], Internet traffic [3,14,16] or 3G networks [2,10]. The key idea is to favor short flows at the expense of long ones because short flows are in general related to interactive applications like Email, Web browsing or DNS requests/responses; unlike long flows which represent background traffic.…”
Section: Introductionmentioning
confidence: 99%
“…While such information is typically available in web servers, it is usually nearly impossible to obtain in Internet routers. An alternative strategy which has therefore been advocated for scheduling data flows is the Least Attained Service first (LAS) discipline also known as ForegroundBackground Processor Sharing (FBPS) [22,27,29,30]. In case the service requirement distribution has a decreasing failure rate, it has been shown that LAS stochastically minimizes the number of jobs in the system among all strategies that use no knowledge of the remaining job sizes [31].…”
Section: Introductionmentioning
confidence: 99%
“…For example, at an online shopping site the large requests are often the shopping cart transactions. The same tradeoff has appeared across diverse computer system application areas, e.g., process scheduling [14], routers [36,37], wireless networks [22], transport protocols [56], and beyond.…”
Section: An Emerging Focus On Fairnessmentioning
confidence: 99%
“…For example, Shortest Remaining Processing Time (SRPT) is well-known to minimize mean response time across general arrival processes and job size distributions [47] and, among non-preemptive policies, Shortest Job First (SJF) optimizes the mean response time [11]. As a result, designs that give priority to jobs with small sizes have been suggested for a variety of computer systems in recent years, such as [20,38,36,37,22,56,14]. However, the adoption of these new designs has been slowed by concerns about the unfairness of these policies.…”
Section: An Emerging Focus On Fairnessmentioning
confidence: 99%
See 1 more Smart Citation